AKIBAT HUKUM TERHADAP PARA PIHAK DALAM PELAKSANAAN LELANG EKSEKUSI HAK TANGGUNGAN YANG DINYATAKAN PERBUATAN MELAWAN HUKUM - Dewi Yulia Andriany Sitorus; Saidin Saidin; Edy Ikhsan (Smart Education, 2024)
Abstract: The dispute between Jamarik as Pelawan and PT. BPR Nusantara Bona Pasogit 22 as Defendant I, KPKNL Medan as Defendant II, and Ernita Citra Dewi Sagala as Defendant III which arose over the issue of the auction procedures and procedures for the execution of collateral objects in the form of land and buildings thereon with Certificate of Ownership Number 374, date 14 October 2010 in the name of Pelawan in accordance with legal provisions. The judge in his legal considerations decided that the auction for the execution of Mortgage Rights carried out by the Medan KPKNL was an unlawful act so that the Auction Minutes Number 1128/2016 issued by the Auction Officer from the Medan KPKNL had no legal force. The cancellation of the auction will certainly have legal consequences for the parties, both for the owner of the object being auctioned, the auction seller and the auction buyer. The conclusion regarding the problem formulated in this journal is that the legal consequences for the parties regarding the cancellation of the Auction Minutes for the execution of Mortgage Rights in case decision Number 951/PK/Pdt/2022 are that for the buyer/winner of the auction, the auction buyer's right to the debtor's auction object will be ends, for the owner of the auction object (debtor), the item being auctioned returns to its original condition to the debtor, but remains in the status of collateral, while for the auction seller (creditor) there is a delay in obtaining the fulfillment of the achievements in the credit agreement. Keywords: Auction, Mortgage Rights, Unlawful Actions Abstrak: Perselisihan antara Jamarik selaku Pelawan melawan PT. BPR Nusantara Bona Pasogit 22 selaku Terlawan I, KPKNL Medan selaku Terlawan II, serta Ernita Citra Dewi Sagala selaku Terlawan III yang timbul atas persoalan apakah prosedur dan tata cara lelang eksekusi terhadap objek jaminan berupa tanah dan bangunan diatasnya dengan Sertifikat Hak Milik Nomor 374, tanggal 14 Oktober 2010 atas nama Pelawan telah sesuai dengan ketentuan hukum. Hakim dalam pertimbangan hukumnya memutuskan bahwa pelaksanaan lelang eksekusi Hak Tanggungan yang dilakukan KPKNL Medan tersebut merupakan perbuatan melawan hukum sehingga Risalah Lelang Nomor 1128/2016 yang dikeluarkan oleh Pejabat Lelang dari KPKNL Medan tidak mempunyai kekuatan hukum. Pembatalan pelaksanaan lelang ini tentu menimbulkan akibat hukum bagi para pihak, baik terhadap pemilik objek yang dilelang, penjual lelang, serta pembeli lelang. Kesimpulan mengenai permasalahan yang dirumuskan di dalam jurnal ini adalah akibat hukum bagi para pihak terhadap pembatalan Risalah Lelang eksekusi Hak Tanggungan dalam putusan perkara Nomor 951/PK/Pdt/2022 adalah bagi pembeli/pemenang lelang, hak pembeli lelang atas objek lelang milik debitor akan menjadi berakhir, bagi pemilik objek lelang (debitor), barang yang dilelang kembali kepada keadaan semula kepada debitor, namun tetap dalam status barang jaminan, sementara bagi penjual lelang (kreditor) terjadi penundaan untuk memperoleh pemenuhan prestasi dalam perjanjian kredit. Kata kunci: Lelang, Hak Tanggungan, Perbuatan Melawan Hukum